(3ecGJHI ef CHj GdTjN GdeYGdis - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3hUdJ ecGJHI GdTjN GdWGgQ GdRci Pi GdfaS GdSGcfI hGdYbd GdRGgQ GdCHi hhbaJ Ydi eVehf aUhdgG hJUaMJ eHGfi BQGFg HeTQhM GdaQhY s
(3BNQgG (B:s
(3hGdTGchf GdPjf BjShG ef QLYJg hdbGFg hbjGeg HSja GdMb JeJ HMeO hdi GdfYeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B102s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis